Правові засади забезпечення превентивної діяльності Національної поліції - Беспалий, І. В.; Bespalyi, I. V. (Європейські перспективи. - 2022. - № 4. - С. 267-272, 2022)
У статті виділено систему нормативно-правових актів різної юридичної сили, які складають правові засади забезпечення превентивної діяльності Національної поліції України. Акцентовано увагу на тому, що на сьогоднішній день регулювання превентивної діяльності Національної поліції потребує покращення, з огляду на що запропоновано внести відповідні зміни до Закону України «Про Національну поліцію».

Attention is focused on the fact that the system of legal bases for ensuring the preventive activities of the National Police of Ukraine consists of a large number of normative legal acts of different legal force, the provisions of which regulate: 1) the powers, directions and tasks of the National Police of Ukraine in the context of preventing and combating crime, and also other offenses, etc.; 2) the procedure and features of the interaction of specially authorized subjects in the researched field; 3) legal status and role of structural bodies and divisions of the National Police in the process of implementing operations and measures of a preventive nature; etc. It was noted that the regulation of preventive activities of the National Police today needs improvement. In particular, there are no provisions in the current regulatory documents that would accurately determine the nature, inner essence and clear internal structure of the specified direction of police law enforcement work. Despite the fact that most of the presented documents establish mechanisms and measures that are logically related to prevention, none of them explicitly mentions this. In addition, even in the targeted Law of Ukraine «On the National Police» preventive activity is used as a concept, but there is no concrete description of this legal phenomenon. Such a negative aspect needs to be eliminated by making changes to the abovementioned Law in the form of supplementing it with norms that would clearly and fully disclose the legal status of the subjects of preventive activity, as well as the specifics of its implementation as a direction of law enforcement activity.

В статье выделена система нормативно-правовых актов различной юридической силы, составляющих правовые основы обеспечения превентивной деятельности Национальной полиции Украины. Акцентировано внимание на том, что на сегодняшний день регулирование превентивной деятельности Национальной полиции требует улучшения. Предложено внести соответствующие изменения в Закон Украины «О Национальной полиции».
Keywords: правові засади; нормативно-правовий акт; правове регулювання; превентивна діяльність; Національна поліції України; legal principles; normative legal act; legal regulation; preventive activity; National Police of Ukraine; правовые основы; нормативно-правовой акт; правовое регулирование; превентивная деятельность; Национальная полиция Украины